Synthesis of bis-amino acid derivatives by Suzuki cross-coupling, Michael addition and substitution reactions - Ferreira, Paula M. T. (2009)
Several bis-amino acids were prepared using a bis-Suzuki coupling (compounds 4-8, 10), a sequential Michael addition and bis-Suzuki coupling (compounds 12, 13) and a Michael addition followed by a substitution reaction (compounds 18, 19). Thus, the pure stereoisomer of the methyl esters of N-(tert-butoxycarbonyl)-beta-bromodehydroaminobutyric acid and dehydrophenylalanine and of N-benzyloxycarbonyl-beta-bromodehydroaminobutyric acid were reacted with 1,4-phenylene-bis-boronic acid or 9,9-dioctyl-9H-fluorene-2,7-bis-boronic acid using modified Suzuki coupling conditions. The corresponding bis-dehydroamino acid derivatives were obtained in good to high yields maintaining the stereochemistry of the starting materials. This reaction was also applied successfully to a brominated dehydrodipeptide and 1,4-phenylene-bis-boronic acid showing that it could be used to create cross-links in peptide chains. An N,N-diacyldehydroalanine derivative was used in a sequential Michael addition and bis-Suzuki coupling giving a p-terphenyl bis-amino acid and a fluorenyl bis-amino acid in good yields. Two bis-alpha,beta-diamino acids were obtained by a Michael addition of 1,2,4-triazole to the methyl esters of N-(4-toluenesulfonyl), N-(tert-butoxycarbonyl) dehydroamino acids followed by treatment with ethylenediamine.